Selection and Comlications of Donor Nephrectomy in Gezira Hospital for Renal Diseases and Surgery - Gassemelseed, Abdelraouf; Ahmed, M EL Imam; O M ansour, Mustafa (Gezira Journal of Health Sciences; Vol 11 No 1 (2015), 2015)
Background : Though various renal replacement therapies are endorsed for the long treatment of ESRD yet the transplantation remains the gold standard. Objectives: generally  to assist in auditing of the programme of renal transplantation in Sudan and specifically to determine the degree of matching between donors and recipients ,to determine the effect of age, sex, relation, occupation and education in donor nephrectomy and to  estimate the incidence of complications in donor nephrectomy. Methods: In this study we reviewed open donor nephrectomy performed in GHRD and S from January 2005 to December 2011 in a descriptive retrospective and prospective study. Around 90 living kidney donors were enrolled in this study, followed for one year. Data concerning the work up, clinical strata, the thematic operative conditions and postoperative follow up sheets were recorded in the platform of the patient sheets and retrieved completely through the master sheet of the study and evaluated via SPSS package version 11.5, every complication was dealt with according to EUA guidelines, the mortality recorded was one patient in this study. Results: of these donors41 were males46% and (49) were females (54%) the minimum age was 18 years and maximum 57 and mean age 30,3years. We noted that donors were found satisfying the EAU criteria of donor’s selection. The complications recorded were anesthetic problems in 2.2%, vascular complications in 2.2%, wound infection in 6.6%, pneumonia in 4.4% and the mortality in the study was 1.1%. Conclusion : 1-selection for living donor nephrectomy is consistent with the international criteria and. 2-The incidence of complications in donors in GHRD and S was found to be comparable to the literature with slight inclination to upper limit.